Family Business Cases Insights and Perspectives from the United Arab Emirates - Alkaabi, Khaula; Ramadani, Veland (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book provides insights into family businesses in the United Arab Emirates (UAE) using a unique collection of case studies that help gain a comprehensive understanding of UAE family firms' profiles and the ways they respond to everyday challenges and future disruptions. Cases treat different issues from the perspective of family businesses, such as succession, innovation, decision-making, strategic orientation, corporate governance, spatial distribution, SDG alignment, etc. Each case contains learning objectives, discussion questions, and suggested readings in order to help readers understand the topic discussed in the respective cases. This book also showcases the five business ecosystem stakeholders that have supported family businesses in the UAE, such as the UAE Government, free zone authorities, university and research institutions, support agencies, and venture capital companies. Professionals as well as MBA students and researchers involved in the study of family businesses will particularly benefit from this book.
Foreword -- Preface -- Chapter 1 Al Masaood Group: Through Diversification and Geographical Expansion to Success -- Chapter 2 Barjeel Aerial Photography Services: A Successful Geospatial Data Acquisition Company -- Chapter 3 Innovation Floor: 4.0 Technologies and Information Solutions -- Chapter 4 Secuira Technologies: Re-innovating Smart Technology -- Chapter 5 Safe City Group: Enable Cities Safety -- Chapter 6 MetaTouch: Successful Transformation from a Research Idea to an Emirati Start-up during the COVID-19 Pandemic -- Chapter 7 The Nayel & Bin Harmal Group: Integrated Services in the Construction Sector -- Chapter 8 DAMAC Group: Symbol of Successful Development -- Chapter 9 Pronto Carwash Company: Your Ride to the Mobility Car Wash Business by Emirati Entrepreneur -- Chapter 10 CADD Emirates Computers: Providing Cutting-Edge Technology Solutions and Services for a Digital-First World -- Chapter 11 Bin Ham Group: Building a Legacy of Excellence in United Arab Emirates Investments -- Chapter 12 ISpatial Tech: GEO-AI Enabled Solutions for Smart Cities -- Chapter 13 Juma Al Majid Holding Group: Story of Success and Achievement -- Chapter 14 M Glory Holding: The Aspiration to Establish an Automobile Manufacturing Industry in the United Arab Emirates.
Keywords: Family-owned business enterprises; Strategic planning; Leadership; Industrial organization; Family Business; Business Strategy and Leadership; Organization